2012
DOI: 10.1039/c2cs15327k
|View full text |Cite
|
Sign up to set email alerts
|

Design of polymeric nanoparticles for biomedical delivery applications

Abstract: Polymeric nanoparticles-based therapeutics show great promise in the treatment of a wide range of diseases, due to the flexibility in which their structures can be modified, with intricate definition over their compositions, structures and properties. Advances in polymerization chemistries and the application of reactive, efficient and orthogonal chemical modification reactions have enabled the engineering of multifunctional polymeric nanoparticles with precise control over the architectures of the individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
1,217
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,510 publications
(1,236 citation statements)
references
References 89 publications
10
1,217
0
9
Order By: Relevance
“…When administrated intravenously, NPs should be sufficiently small (100-300 nm) to passively cross the tumor endothelial barrier and then retain in the tumor bed for prolonged time due to 22 reduced lymphatic drainage, which is known as the enhanced permeability and retention effect (Kobayashi et al, 2014). Particles larger than 1 µm are not convenient for intravascular delivery of drugs, since they can readily be opsonized with a possibility of capillary occlusion, while NPs smaller than 5 nm can be cleared rapidly from the blood via extravasation or renal clearance (Elsabahy and Wooley, 2012).…”
Section: Microscopic Images Of Npsmentioning
confidence: 99%
“…When administrated intravenously, NPs should be sufficiently small (100-300 nm) to passively cross the tumor endothelial barrier and then retain in the tumor bed for prolonged time due to 22 reduced lymphatic drainage, which is known as the enhanced permeability and retention effect (Kobayashi et al, 2014). Particles larger than 1 µm are not convenient for intravascular delivery of drugs, since they can readily be opsonized with a possibility of capillary occlusion, while NPs smaller than 5 nm can be cleared rapidly from the blood via extravasation or renal clearance (Elsabahy and Wooley, 2012).…”
Section: Microscopic Images Of Npsmentioning
confidence: 99%
“…[7] Synthesis of poly(L-methionine) 65 Since it has been shown that end-capping is quantitative for (PMe 3 ) 4 Co initiated NCA polymerizations when excess isocyanate is used, [15] integrations of methionine resonances versus the polyethylene glycol resonance at δ 3.64 could be used to obtain the M segment length. [6] The average composition of the copolymer was then determined by 1 conjugated to thioether groups of methionine side chains via an alkylation reaction. [7] M 65 (L 0.5 /F 0.5 ) 20 (10 mg) was dissolved in DMF (1 mL) in a 20 mL scintillation vial.…”
Section: Methodsmentioning
confidence: 99%
“…For successful translation to applications, it is critical that these carriers incorporate many levels of functionality, such as cellular uptake or triggered disruption, which often requires use of complex chemistries and designs. [1] Synthetic carriers prepared solely from natural components that are resorbable and biocompatible are desirable, yet preparation of such materials can be challenging. [2] Here, we developed a method to prepare nanoscale vesicles composed of block copolypeptides using simple and economical chemistry based on the efficient, chemoselective, and broad scope alkylation of methionine residues.…”
Section: Introductionmentioning
confidence: 99%
“…Construction of self‐assembled nanomaterials aiming to biomedical applications is attractive ever‐growing interests, including various biosensing/imaging probes, drug delivery systems, tissue engineering materials for the purpose of diagnosis and therapy 1, 2, 3, 4, 5. On demand of precise medicine with sensitive/selective diagnosis and targeting therapy, development of activatable theranostic nanoagents that can undergo an intrinsic evolution upon cell uptake is highly imperative 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%